VECM MODEL IN MEASURING THE IMPACT OF MONETARY POLICY INTERVENTION ON ECONOMIC GROWTH IN INDONESIA FROM 2009 TO 2022 - Leasiwal, Teddy Christianto; Mail, Johana; Assel, M. Ridwan; Leiwakabessy, Erly; Payapo, Rukmuin W. (International Journal of Social Service and Research, 2024)
This research was conducted to determine the short-term and long-term effects of inflation, exchange rates, interest rates, and the money supply on economic growth in Indonesia from 2009 to 2022 using the Vector Error Correction Model (VECM) method. The VECM method is used to analyze the interaction between these variables over different time horizons, offering valuable insights into their respective roles in influencing economic growth. The results show that in the short run, the exchange rate variable does not have a significant effect on the economic growth, while in the long run the interest rate variable has a positive impact on the economy with a negative coefficient value. The short run variable interest rates do not have significant effects on the growth of the economy, but in the longer run interest rates have an important effect on growth. In conclusion, the effect of exchange rates on the Indonesian economy is still a controversial research topic. The findings enhance the current literature on macroeconomic policy and provide a foundation for policymakers to design more effective economic strategies, especially in addressing the challenges posed by inflation and exchange rate volatility in both the short and long terms.